Combating cancer immunotherapy resistance: a nano‐medicine perspective - Xiangyi Kong; Xintong Xie; Juan Wu; Xiangyu Wang; Wenxiang Zhang; Shuowen Wang; Daria Valerievna Abbasova; Yi Fang; Hongnan Jiang; Jidong Gao; Jing Wang (Cancer Communications)
Abstract Cancer immunotherapy offers renewed hope for treating this disease. However, cancer cells possess inherent mechanisms that enable them to circumvent each stage of the immune cycle, thereby evading anti‐cancer immunity and leading to resistance. Various functionalized nanoparticles (NPs), modified with cationic lipids, pH‐sensitive compounds, or photosensitizers, exhibit unique physicochemical properties that facilitate the targeted delivery of therapeutic agents to cancer cells or the tumor microenvironment (TME). These NPs are engineered to modify immune activity. The crucial signal transduction pathways and mechanisms by which functionalized NPs counteract immunotherapy resistance are outlined, including enhancing antigen presentation, boosting the activation and infiltration of tumor‐specific immune cells, inducing immunogenic cell death, and counteracting immunosuppressive conditions in the TME. Additionally, this review summarizes current clinical trials involving NP‐based immunotherapy. Ultimately, it highlights the potential of nanotechnology to advance cancer immunotherapy.